CD137 differentially regulates innate and adaptive immunity against Mycobacterium tuberculosis - Fernández Do Porto, Darío Augusto (2012)
Protective immunity against Mycobacterium tuberculosis is primarily mediated by the interaction of antigen-specific T cells and antigen presenting cells, which often depends on the interplay of cytokines produced by these cells. Costimulatory signals represent a complex network of receptor-ligand interactions that qualitatively and quantitatively influence immune responses. Thus, here we investigated the function of CD137 and CD137L, molecules known to have a central role in immune regulation, during human tuberculosis (TB). We demonstrated that M. tuberculosis antigen stimulation increased both CD137 and CD137L expression on monocytes and NK cells from TB patients and healthy donors, but only up-regulated CD137 on T lymphocytes. Blockage of the CD137 pathway enhanced the levels of interferon (IFN)-γ and tumor necrosis factor (TNF)-α produced by monocytes and NK against M. tuberculosis. In contrast, CD137 blockage significantly decreased the specific degranulation of CD8 + T cells and the percentage of specific IFN-γ and TNF-α producing lymphocytes against the pathogen. Furthermore, inhibition of the CD137 pathway markedly increased T-cell apoptosis. Taken together, our results demonstrate that CD137:CD137L interactions regulate the innate and adaptive immune response of the host against M. tuberculosis. © 2012 Australasian Society for Immunology Inc. All rights reserved.